TAXONOMICAL, PHYTOCHEMICAL, ANTIOXIDANT AND ANTIBACTERIAL STUDY OF SOME MEDICINAL PLANTS OF THE MYRTACEAE FAMILY (Nativa, 2024)
This paper addresses a comparative study of three medicinal plants of the myrtle family (Callistemon macropunctatus Dum. Cours. Court; Eucalyptus camaldulensis Dehnh.; Myrtus communis L.). The morphological characteristics of the pollen grains and some anatomical characteristics of the leaves and stems were evaluated, with quantitative estimates of the phenolic and flavonoid compounds of the leaves and determination of the efficacy of the aqueous-alcoholic extract of the leaves as an antioxidant based on the DPPH method; in addition, the efficacy of the extract as an antibacterial for some pathogenic strains, Gram-positive (Staphylococcus aureus and Klebsiella pneumonia) and Gram-negative (Pseudomonas aeruginosa and Escherichia coli) was evaluated. The results showed the taxonomic importance of pollen grain characteristics in separating the Myrtus communis species and the effective role of anatomical characteristics in separating the studied genera. Furthermore, the study's results showed the efficacy of the leaf extract of the studied genera as a strong antioxidant and an effective antibacterial for both types of pathogenic bacterial strains. The greatest efficacy of the extract was for the leaves of the Myrtus communis species due to the high content of phenolic compounds and flavonoids. Keywords: Myrtaceae; Callistemon macropunctatus; Myrtus communis; Eucalyptus camaldulensis; antioxidant. EEstudo taxonômico, fitoquímico, antioxidante e antibacteriano de algumas plantas medicinais da família Myrtaceae RESUMO: Este trabalho aborda um estudo comparativo de três plantas medicinais da família das murtas (Callistemon macropunctatus Dum. Cours. Court; Eucalyptus camaldulensis Dehnh.; Myrtus communis L.). Foram avaliadas as características morfológicas dos grãos de pólen e algumas características anatômicas das folhas e caules, com estimativas quantitativas dos compostos fenólicos e flavonoides das folhas e determinação da eficácia do extrato aquoso-alcoólico das folhas como antioxidante com base no método DPPH; além disso, avaliou-se a eficácia do extrato como antibacteriano para algumas cepas patogênicas, Gram-positivas (Staphylococcus aureus and Klebsiella pneumonia) e Gram-negativas (Pseudomonas aeruginosa and Escherichia coli). Os resultados mostraram a importância taxonômica das características dos grãos de pólen na separação da espécie Myrtus communis e o papel efetivo das características anatômicas na separação dos gêneros estudados. Além disso, os resultados do estudo mostraram a eficácia do extrato de folhas dos gêneros estudados como um forte antioxidante e um antibacteriano eficaz para ambos os tipos de cepas bacterianas patogênicas. A maior eficácia do extrato foi para as folhas da espécie Myrtus communis devido ao alto teor de compostos fenólicos e flavonoides.Palavras-chave: Myrtaceae; Callistemon macropunctatus; Myrtus communis; Eucalyptus camaldulensis; antioxidante.